The international and domestic fabrics of an ideological illusion: the Socialist MPLA (Revista Tempo e Argumento, 2021)
The political-ideological characterization and analysis of Angolan nationalist movements and the conflicts between them, has always been subject of major and passionate political-academic discussion, which became an important component of the nationalist movements’ international and domestic characterization and definition. The MPLA (Popular Movement for the Liberation of Angola) rapidly acquired the epithet of leftist, Socialist and Marxist since the anti-colonial struggle through the independence and afterwards. However, during the so-called founding period of an officially proclaimed Socialist MPLA, in an apparent contradiction, the MPLA’s governing practice went objectively in an opposite direction, while still reinforcing that unquestioned epithet of Socialist. It is here argued that foreign attributed classifications (political and academic), influenced by the passionate political-idological struggles of the 1950s, 1960s and 1970s, the civil war and the Cold War, ended up diplomatically-politically assumed (instrumentalised) by the movement itself, whereby an illusive characterization/identification prevailed, hampering a more objective analysis of the post-independence political practice. Our paper will focus on the contrast between the academic discussion on the political-ideological characterization of the MPLA (part I) and the governing practice of the party during the administration of the first President of the Republic, which was the founding period of the MPLA as a so-called Marxist-Leninist Socialist party (part II).Keywords: Angola; MPLA; Socialism; Agostinho Neto administration; political orientation.